Fusion of Landsat 8 Operational Land Imager and Geostationary Ocean Color Imager for hourly monitoring surface morphology of lake ice with high resolution in Chagan Lake of Northeast China - Q. Yang; Q. Yang; X. Shi; X. Shi; W. Li; K. Song; Z. Li; X. Hao; F. Xie; N. Lin; Z. Wen; C. Fang; et al. (The Cryosphere, 2023)
The surface morphology of lake ice remarkably changes under the combined influence of thermal and mechanical forces. However, research on the surface morphology of lake ice and its interaction with climate is scarce. A large-scale linear structure has repeatedly appeared on satellite images of Chagan Lake in recent years. The Geostationary Ocean Color Imager (GOCI), with a 1 h revisit, and Landsat 8 Operational Land Imager (OLI), with a spatial resolution of 30 m, provide the possibility for the study of hourly changes in the large-scale linear structure. We merged the Landsat and GOCI images, using an Enhanced Spatial and Temporal Adaptive Reflectance Fusion Model (ESTARFM), and extracted the lengths and angles of the linear structure. We monitored the hourly changes in the surface morphology during the cold season from 2018 to 2019. The average length of the linear structure in the completely frozen period was 21 141.57 ± 68.36 m. The average azimuth angle was 335.48 ± 0.23∘, nearly perpendicular to the domain wind in winter. Through two field investigations during the two recent cold seasons, we verified the linear structure as being ice fractures and ridges. The evolution of surface morphology is closely associated with air temperature, wind, and shoreline geometry.